MODEL INDEKS LIKUIFAKSI BERBASIS STANDARD PENETRATION TEST MENGGUNAKAN MULTI-GENE GENETIC PROGRAMMING - Bosco Hendro; Widjojo A. Prakoso (Racic : Rab Construction Research, 2023)
Earthquake and series of specific phenomena in Palu and any other parts of the world contributed to a liquefaction that was involving massive fatalities and economic loss. The evaluation of liquefaction potential based on standard penetration test (SPT) data using deterministic approach has been widely applied. A liquefaction index model is required for the determination of a limit state between liquefaction and non-liquefaction cases by the consideration of bias issues in deterministic method. This research is aimed at the determination of liquefaction index model in relating (N1)60 and CSR7.5 using multi-gene genetic programming (MGGP) to develop limit state curve and its comparison with previous studies. The developed liquefaction index model based on SPT data using MGGP resulted in a performance in terms of successful prediction of 93% for testing of datasets.